IMPROVEMENT OF METHODOLOGICAL APPROACHES IN THE TRAINING OF FUTURE COMPUTER SCIENCE TEACHERS - Farmanov Sardorbek Utkir oglu (Bright Mind Publishing, 2025)
This article examines the importance of methodological approaches in training future computer science teachers, their adaptation to modern educational requirements, and effective ways to integrate them into the educational process. The study developed proposals for pedagogical technologies, innovative teaching methods, the use of digital resources, and methodological support for practical classes. The advantages of a constructive approach, active learning methods, and a problem-based learning curriculum in developing the professional competencies of computer science teachers are analyzed. The paper presents methodological recommendations for improving the effectiveness of education and analyzes important aspects of their contribution to the modernization of teaching.
Keywords: Digital technologies, information, cloud technologies, digital educational resources, educational portals, artificial intelligence, didactic principles, competencies, knowledge, skills and qualifications.